2003
DOI: 10.1523/jneurosci.23-36-11411.2003
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Locomotion in the Intact and Spinal Mouse

Abstract: Because the genetic characteristics of several inbred strains of mice are well identified, their use is becoming increasingly popular in spinal cord injury research. In this context, it appears particularly important to document adequately motor patterns, such as locomotion in normal mice, to establish some baseline values of locomotor characteristics. It also seems crucial to determine the extent to which mice can express a locomotor pattern after a complete spinal transection to establish a baseline on which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(178 citation statements)
references
References 44 publications
7
166
3
Order By: Relevance
“…However, 'off-line' kinematic analysis methods may be useful for completely untrained observers or if higher levels of recovery are to be found due to treatments or training. 10 Altogether, this method offers fair advantages over other methods for 'drug-screening' studies where large number of protocols or treatments are to be tested and compared in complete spinal cord transected animals (eg, effects of various types of training and drug treatment on central pattern generator activation).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, 'off-line' kinematic analysis methods may be useful for completely untrained observers or if higher levels of recovery are to be found due to treatments or training. 10 Altogether, this method offers fair advantages over other methods for 'drug-screening' studies where large number of protocols or treatments are to be tested and compared in complete spinal cord transected animals (eg, effects of various types of training and drug treatment on central pattern generator activation).…”
Section: Discussionmentioning
confidence: 99%
“…Movement amplitude was evaluated qualitatively, as for other assessment methods in open-field condition (eg, BBB, adapted motor score, Tarlov, etc), since detailed 2-D kinematic analyses would require movements to be performed on a treadmill. 10 Movement amplitude was characterized by assigning one of three values; 0 -if no movement was observed; 1 -if the amplitude of most movements was less than half the range of motion of normal steps; 2 -if the amplitude of most movements was at least more than half the range of motion of normal steps. 'Movement incidence' was defined as the total number of mice that displayed movements (NBA or BA) over all tested mice of the same group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is one exception to this generalization. Leblond et al (2003) reported that adult spinal mice "can express hindlimb locomotion within 14 days of spinalization" and have "similar angular excursions of the hip, knee and ankle as intact mice". However, full weight-bearing on the hindlimbs was not observed in that the authors stated "the animal has to be supported and a lateral stability has to be provided by the experimenters".…”
Section: Introductionmentioning
confidence: 99%